Big Book Media for Optimizing Reading Literacy in Grade III Students of Madrasah Ibtidaiyah - Firmansah, Deri; Nur Kalifah, Diah Rizki (FONDATIA, 2024)
In today's digital era, although technology brings various benefits, reading literacy among students, especially at the elementary level, has experienced an alarming decline. This condition also has an impact on elementary school students who are more interested in digital entertainment than reading books, which ultimately affects their motivation and literacy skills. This study aims to develop Big Book media and test its effectiveness in improving reading literacy of grade III students at Madrasah Ibtidaiyah. This study uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were grade III students at Madrasah Ibtidaiyah Negeri 6 Bandar Lampung consisting of two classes, with a total of 60 students. Data were collected through observation, interviews, questionnaires, and documentation. The research instrument used a validation questionnaire by experts, teacher responses and student responses. To determine the score in the expert validation questionnaire and teacher and student responses, the data was analyzed using a Likert scale while to test the effectiveness of the product/product feasibility using a pretest and posttest with the N-gain test. The validation results showed that this media was very feasible to use, with a validation percentage of material experts of 91.5%, media experts of 84.75%, and language experts of 89%. Small and large-scale trials gave average results of 91% and 92% respectively, which were categorized as "Very Feasible". The results of the pretest and posttest analysis showed an increase in the N-Gain score in the "Medium" category for both classes. These findings indicate that the Big Book media is effective in increasing interest and reading literacy skills.